INCORPORATION OF VITAMIN E ONTO CROSS-LINKED GALACTOMANNAN PHOSPHATE MATRIX AND IN VITRO STUDY - Tarigan, Juliati Br; Purba, Djendakita; Zuhra, Cut Fatimah (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: This study demonstrated the incorporation of Vitamin E from palm fatty acid distillate onto crosslinked galactomannan phosphate (CGP) matrix. Methods: CGP was obtained from the crosslinking reaction of galactomannan from Arenga pinnata (GAP) with tri-sodium metaphosphate (TMF) ranging from 1:1 to 4:3 while incorporation of Vitamin E was conducted in two steps to form films. The reliability study of Vitamin E in CGPVE was conducted using a solution of pepsin and sodium chloride and also in solution of pancreatin and buffer phosphate. Results: The Fourier-transform infrared spectrum indicated the presence of phosphate in CGP while the scanning electron microscope images depicted the changes of surface morphology from smooth (GAP) to rough and hollow (CGP) which confirmed that crosslink had occurred. The swelling study of CGP showed that the swelling indexes were similar and decreased with the increase of TMF. The efficiency of CGP to absorb Vitamin E ranged from 89.66% to 91.09%. The in vitro releasing study of Vitamin E in simulated gastric fluid and simulated intestinal fluid showed that only a small amount of Vitamin E was released. Conclusions: This study demonstrated that CGP can be prepared and is potentially useful for drug delivery to the colon.